Answer:
3c + 2x + 11
Step-by-step explanation:
Answer: Type the questions please and take a clearer photo
Step-by-step explanation:
Answer:
using cos=adjacent/hypotenuse
Step-by-step explanation:
in this case cos(60)=x/4√3
x=cos(60)*4√3
x=3.46
Hey there!
We have 10 pieces of paper. The probability of drawing a 10 is 1/10. Therefore, if we were to draw ten times, the ten should probably be drawn once. If we multiplied our number of drawings by four (10*4=40), our outcome of seeing our slip with the ten should also quadruple and become four times. (1*4=4)
I hope that this helps! Have an awesome day!
Solve for <em>x</em> when √(<em>x</em> ² - 4) = 1 :
√(<em>x</em> ² - 4) = 1
<em>x</em> ² - 4 = 1
<em>x</em> ² = 5
<em>x</em> = ±√5
We're looking at <em>x </em>≤ 0, so we take the negative square root, <em>x</em> = -√5.
This means <em>f</em> (-√5) = 1, or in terms of the inverse of <em>f</em>, we have <em>f</em> ⁻¹(1) = -√5.
Now apply the inverse function theorem:
If <em>f(a)</em> = <em>b</em>, then (<em>f</em> ⁻¹)'(<em>b</em>) = 1 / <em>f '(a)</em>.
We have
<em>f(x)</em> = √(<em>x</em> ² - 4) → <em>f '(x)</em> = <em>x</em> / √(<em>x</em> ² - 4)
So if <em>a</em> = -√5 and <em>b</em> = 1, we get
(<em>f</em> ⁻¹)'(1) = 1 / <em>f '</em> (-√5)
(<em>f</em> ⁻¹)'(1) = √((-√5)² - 4) / (-√5) = -1/√5
The sign must be negative; see the attached plot, and take note of the negatively-sloped tangent line to the inverse of <em>f</em> at <em>x</em> = 1.